FACTORS RESPONSIBLE FOR CAREER SWITCH TO NON-COMMUNICATION RELATED JOBS BY THE GRADUATES OF MASS COMMUNICATION AND JOURNALISM - AWOFADEJU PETER OLAYINKA; Philip O. Ewuola (IJRDO - Journal of Social Science and Humanities Research, 2019)
This research was carried out to examine the factors responsible for career switch to non-communication related jobs by the graduates of mass communication and journalism, using the students of Osun State Polytechnic, Iree, Osun State as the case study. Survey method of gathering data was adopted for this paper by distributing well-developed questionnaire to elicit responses from the respondents, the sample size of which was 120. The findings clearly showed that graduates of mass communication or journalism switch career to non-communication related jobs mostly because of poor journalists’ welfare package in Nigeria and many fresh graduates of mass communication or journalism choose not to practice within their profession but switch to other careers immediately after graduation, while others who decide to remain and practice within their profession only spend no more than ten years within their profession before they switch career to other areas of work such as teaching in schools or academic institutions, working in banks or financial institutions, etc. Other factors that are responsible for their career switch were also discussed.